2019
DOI: 10.1111/ivb.12237
|View full text |Cite
|
Sign up to set email alerts
|

How do gastropods grow synchronized shell sculpture? Effect of experimental varix manipulations on shell growth byCeratostoma foliatum(Muricidae: Ocenebrinae)

Abstract: Gastropod shells display striking patterns in both color and sculpture, but rather little is known about the developmental mechanisms that produce those patterns. Here, we tested a physical feedback hypothesis for how snails control spatial patterning of shell sculpture. Varices—a form of synchronized, blade‐like axial sculpture—are produced at regular intervals around the shell and often aligned closely between adjacent whorls. Older varices were believed to provide a spatial cue about where to position a new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…It should be noted also that physical cues in marine gastropod shells possessing varices (thickened protrusions of shell) do not appear to be the main mechanism used to position new shell structures. Instead, it has been suggested that positional information of these structures is created by a Turinglike system, but with previous shell structures providing some finetuning feedback (Webster & Palmer, 2019).…”
Section: Reaction Diffusion Mechanismmentioning
confidence: 99%
“…It should be noted also that physical cues in marine gastropod shells possessing varices (thickened protrusions of shell) do not appear to be the main mechanism used to position new shell structures. Instead, it has been suggested that positional information of these structures is created by a Turinglike system, but with previous shell structures providing some finetuning feedback (Webster & Palmer, 2019).…”
Section: Reaction Diffusion Mechanismmentioning
confidence: 99%
“…In dextrally coiled univalved shells, the left side of the mantle (on the inner‐lip or columellar side) dissolves skeletal material on the outer shell surface as the edge of the inner lip expands over the exposed whorl during spiral growth. As a result, external sculpture is partially or wholly removed before the surface is glazed over by the mantle or foot epithelium (Carriker 1972; Webster & Palmer 2019). This kind of surficial dissolution is widespread in gastropods (Signor 1982) and coiled shell‐bearing cephalopods (Signor 1985; Radtke et al .…”
Section: Taxonomic Surveymentioning
confidence: 99%